2016
DOI: 10.1038/nature19106
|View full text |Cite
|
Sign up to set email alerts
|

A terrestrial planet candidate in a temperate orbit around Proxima Centauri

Abstract: At a distance of 1.295 parsecs, 1 the red-dwarf Proxima Centauri (α Centauri C, GL 551, HIP 70890, or simply Proxima) is the Sun's closest stellar neighbour and one of the best studied low-mass stars. It has an effective temperature of only ∼ 3050 K, a luminosity of ∼0.1 per cent solar, a measured radius of 0.14 R ⊙ 2 and a mass of about 12 per cent the mass of the Sun. Although Proxima is considered a moderately active star, its rotation period is ∼ 83 days, 3 and its quiescent activity levels and X-ray lumin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
784
1
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,202 publications
(812 citation statements)
references
References 62 publications
15
784
1
2
Order By: Relevance
“…CODEX, Pasquini et al 2010). As the radial velocity resolution decreases, the resultant noise from stellar activity in Sun-like stars becomes significant (Dumusque et al 2011a;Anglada-Escudé et al 2016). We do not consider stellar noise in our assessment herein.…”
Section: Exoplanet Populationmentioning
confidence: 99%
“…CODEX, Pasquini et al 2010). As the radial velocity resolution decreases, the resultant noise from stellar activity in Sun-like stars becomes significant (Dumusque et al 2011a;Anglada-Escudé et al 2016). We do not consider stellar noise in our assessment herein.…”
Section: Exoplanet Populationmentioning
confidence: 99%
“…The rotation period of Proxima is nevertheless uncertain. The rotation period is of interest for various studies, including flare cycles (Davenport et al 2016) and for the correct identification of radial velocity signals from orbiting planets (Anglada-Escudé et al 2016) and subsequent work (Ribas et al 2016). Previous studies have reported periods ranging from 31.5 ± 1.5 days (Guinan & Morgan 1996), through 41.3 days (Benedict et al 1993) to between 82 and 84 days (Benedict et al 1992(Benedict et al , 1998.…”
Section: Introductionmentioning
confidence: 99%
“…This topic is particularly timely given the recent discoveries of likely terrestrial planets in the habitable zones of three M-dwarfs within 40 light years of Earth (TRAPPIST-1e, Proxima Centauri b, and LHS 1140b, Anglada-Escudé et al 2016;Gillon et al 2017;Dittmann et al 2017). One issue that influences planetary habitability is the occurrence of global glaciations, which are called snowball Earth events in Earth history (Kirschvink 1992;Hoffman et al 1998).…”
Section: Introductionmentioning
confidence: 99%